Server architectures multiprocessors, clusters, parallel systems, Web servers, and storage solutions - Chevance, Rene J. (Amsterdam ; Boston : Elsevier/Digital Press, 2005)
The goal of this book is to present and compare various options one for systems architecture from two separate points of view. One, that of the information technology decision-maker who must choose a solution matching company business requirements, and secondly that of the systems architect who finds himself between the rock of changes in hardware and software technologies and the hard place of changing business needs. Different aspects of server architecture are presented, from databases designed for parallel architectures to high-availability systems, and touching en route on often- neglected performance aspects. 1. The book provides IT managers, decision makers and project leaders who want to acquire knowledge sufficient to understand the choices made in and capabilities of systems offered by various vendors: 2. Provides system design information to balance the characteristic applications against the capabilities and nature of various architectural choices 3. In addition, it offers an integrated view of the concepts in server architecture, accompanied by discussion of effects on the evolution of the data processing industry.
Cover -- Copyright Page -- Contents -- Preface -- Objective of the Book -- A Changing Industry Based on Changing Technology -- Structure of the book -- Origin of the Book -- Server FAQs -- Introduction -- Transaction Processing and Decision Support -- Web Servers -- Selection Criteria -- Endnotes -- Part 1: Architectural Options and Technology Evolution -- P.1 Systems Architecture Basics -- P.2 Historical Notes about System Architecture -- P.3 Endnotes -- Chapter 1. Processors and Memory -- 1.1 Semiconductors and Microprocessors -- 1.2 Semiconductor Technology Projections -- 1.3 Economic Aspects of Microprocessors -- 1.4 Embedded Systems -- 1.5 Memory Hierarchy -- 1.6 The Problem of Memory Throughput -- 1.7 Processor-Memory-I/O Interconnect -- 1.8 Parallelism -- 1.9 Binary Compatibility Constraints-Java and Architecture Retargeting -- 1.10 Compilation and Interpretation -- 1.11 Java -- 1.12 Architecture Retargeting -- 1.13 Microprocessor Evolution -- 1.14 Economic Factors -- 1.15 Formal Verification -- 1.16 Memory -- 1.17 Endnotes -- Chapter 2. I/O -- 2.1 PCI, SCSI, and Fibre Channel -- 2.2 SCSI and Fibre Channel -- 2.3 ATA -- 2.4 A New I/O Architecture: InfiniBand -- 2.5 Virtual Interface Architecture -- 2.6 Data Storage -- 2.7 Networks and Communications Subsystems -- 2.8 Input Output Evolution -- 2.9 Endnotes -- Chapter 3. Evolution of Software Technology -- 3.1 Virtual Memory and 64-Bit Architecture -- 3.2 Operating Systems -- 3.3 Client/Server Applications and Middleware -- 3.4 Security -- 3.5 Systems Administration -- 3.6 Software Evolution -- 3.7 Endnotes -- Part 2: System Architecture Options -- Chapter 4. Symmetrical (Tightly-Coupled) Multiprocessors -- 4.1 SMPs: Hardware Limitations -- 4.2 Adapting Software to an SMP -- 4.3 SMP Architectures with a Moderate Number of Processors (<= 8) -- 4.4 Multiprocessors with Many Processors (More than 16) -- 4.5 SMP, CC-NUMA, COMA: a Summary -- 4.6 Performance Improvement Provided by SMP -- 4.7 Advantages and Disadvantages of SMP Architecture -- 4.8 Endnotes -- Chapter 5. Clusters and Massively Parallel Machines -- 5.1 Clusters -- 5.2 Advantages and Disadvantages of Cluster Architecture -- 5.3 Massively Parallel Machines (MPP) -- 5.4 Advantages and Disadvantages of MPP Architecture -- 5.5 Networks Used to Build Supercomputers -- 5.6 SMPs, Clusters, and MPPs-a Summary -- 5.7 Flexible SMP-Cluster Architecture -- 5.8 Endnotes -- Chapter 6. Data Storage -- 6.1 Data Storage -- 6.2 Storage Issues -- 6.3 Functional Levels: File Systems -- 6.4 Optimized File Systems: Log Structured File System -- 6.5 Parallel File Systems -- 6.6 Remote File Access: NFS, CIFS and DAFS -- 6.7 JBOD, SBOD, and RAID Disk Organization -- 6.8 Storage Virtualization -- 6.9 Scatter Reads and Gather Writes -- 6.10 Comparing the Various RAID Levels -- 6.11 Perform.
Includes bibliographical references and index.
Keywords: Computer architecture; System design; Client/server computing; Electronic books